2011
DOI: 10.1111/j.1753-4887.2011.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing whole diets of young children from developed countries and the association between diet and health: a systematic review

Abstract: Early childhood is an important nutritional period that involves the transition from a milk-based diet to ordinary foods. A systematic review was conducted of studies that applied whole-of-diet analysis of children aged 1-5 years to examine associations between diet and nutrition, health, and development. Literature searches identified 40 articles using dietary indices, principal component analysis, or cluster analysis. Reports that applied indices (n = 23, 18 indices) were cross-sectional, and most measured d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
134
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 70 publications
(493 reference statements)
10
134
1
2
Order By: Relevance
“…Eligible studies were identified in the literature published between 1970 and June 2013 using electronic searches of PubMed and Web of Science (English language only) and the following search terms: dietary patterns; PCA; FA; RRR; children; adolescents; obesity; BMI; overweight; weight. Reference lists in eligible articles and relevant reviews (16,17) were also hand searched. Studies on growth confined to infancy were excluded.…”
Section: Identifying the Literaturementioning
confidence: 99%
“…Eligible studies were identified in the literature published between 1970 and June 2013 using electronic searches of PubMed and Web of Science (English language only) and the following search terms: dietary patterns; PCA; FA; RRR; children; adolescents; obesity; BMI; overweight; weight. Reference lists in eligible articles and relevant reviews (16,17) were also hand searched. Studies on growth confined to infancy were excluded.…”
Section: Identifying the Literaturementioning
confidence: 99%
“…4 A systematic review of studies on diets of well-nourished children ,5 years of age from developed countries identified a prevalence of incomplete adherence to dietary guidelines, indicating that there is room for improvement. 5 Docosahexaenoic acid (DHA) has been associated with improved immune outcomes and fewer respiratory infections in infants and children. [6][7][8][9] Previous studies of children ,6 years of age in the United States have reported inadequate intake of DHA and corresponding low DHA status.…”
mentioning
confidence: 99%
“…Both, the exclusive BF and sufficient complementary feeding (in quality and quantity) are some factors that promote adequate growth and physical composition 19 .…”
Section: Breastfeeding and Obesitymentioning
confidence: 99%